IMPLEMENTASI METODE DEBAT AKTIF PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - M. Zulfikor (UNISAN JURNAL, 2024)
The point of this examination is to figure out why the utilization of dynamic learning methodologies has not had the option to further develop understudy learning accomplishment at SMA Negeri 1 Palembang City. This exploration is expressive subjective field examination or pondering how to carry out dynamic learning methodologies to further develop understudy learning accomplishment. In this examination, the information assortment strategies utilized were perception, meetings and documentation. The information got is then handled through information decrease, show, check and reaching determinations. In light of the depiction introduced above, it very well may be presumed that the scientist tracked down significant focuses in carrying out dynamic learning systems in further developing understudies' ethical conviction learning accomplishment at SMA Negeri 1 Palembang City. The elements that impact the low expansion in understudy learning accomplishment at SMA Negeri 1 Palembang City are: Educators' regard for latent understudies is as yet deficient with regards to, educators don't comprehend the potential that understudies really have, frequently measure understudies' capacities utilizing principles that surpass reality, so understudies dazzled. should have the option to, the utilization of media to help learning exercises isn't ideal, educators actually rule instructing and learning exercises, the language utilized by instructors is less informative, clarifications about assessment rules, particularly exercises that understudies should do, are deficient. Dynamic learning methodologies, whenever carried out ideally, will get a decent reaction from understudies. This is shown by the rising reaction of understudies at each gathering. And that's only the tip of the iceberg and more understudies are getting scores over the standard score that has been set at SMA Negeri 1 Palembang City, in particular 65.